Academic Senate Minutes 2006-08-31 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 5/24/06 amended and approved. Faculty Eligible for Emeritus status Approved. End of Year Reports: SAC, SPC, FSSP, SBC, and Senate. Update on WASC. Crash Course on Robert's Rules ppt. Election of Senators to Executive Committee. Senator Daley volunteered to attend Student Senate. Composition of the Task Force to study the 4-unit conversion. Resolution Regarding Faculty Boycott of SSU Barnes and Noble Bookstore First Reading. Provost Report. Vice President of Administration and Finance report. Associated Students report. Chair-Elect report. Statewide Senators report. FSAC report. Group photo.